2022
DOI: 10.1007/s12020-022-03107-7
|View full text |Cite
|
Sign up to set email alerts
|

Iodine as a potential endocrine disruptor—a role of oxidative stress

Abstract: Purpose Iodine is an essential micronutrient required for thyroid hormone biosynthesis. However, overtreatment with iodine can unfavorably affect thyroid physiology. The aim of this review is to present the evidence that iodine—when in excess—can interfere with thyroid hormone synthesis and, therefore, can act as a potential endocrine-disrupting chemical (EDC), and that this action, as well as other abnormalities in the thyroid, occurs—at least partially—via oxidative stress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 190 publications
0
11
0
Order By: Relevance
“…The central role of iodide in thyroid physiology has been known for many years. The iodine atoms constitute 65% and 59% of T4 and T3 by weight respectively, and -as extensively demonstrated in previous studies -both iodine excess and de ciency strongly predispose to the development of thyroid dysfunction [3]. Around 15-20% of amiodarone-treated patients develop either thyrotoxicosis (AIT) or hypothyroidism (AIH), that can arise either early or late during treatment and in apparently normal thyroid glands or in the presence of underlying thyroid pathologies [4,5].…”
Section: Introductionmentioning
confidence: 74%
“…The central role of iodide in thyroid physiology has been known for many years. The iodine atoms constitute 65% and 59% of T4 and T3 by weight respectively, and -as extensively demonstrated in previous studies -both iodine excess and de ciency strongly predispose to the development of thyroid dysfunction [3]. Around 15-20% of amiodarone-treated patients develop either thyrotoxicosis (AIT) or hypothyroidism (AIH), that can arise either early or late during treatment and in apparently normal thyroid glands or in the presence of underlying thyroid pathologies [4,5].…”
Section: Introductionmentioning
confidence: 74%
“…It was found that lipid oxidation, the degradation of ascorbic acid, and changes in protein functions could be mediated through the presence of iodate. Additionally, it was confirmed that iodate in high concentrations with herbs damages rat thyroid follicular cells less, which may be related to the oxidant activity of iodate and the high antioxidant capacity of these herbs [28].…”
Section: Antioxidant Activity Directly After Drying and After 320 Day...mentioning
confidence: 88%
“…Children with biochemical evidence of iodine deficiency experience a higher level of oxidative stress than their healthy peers with iodine sufficiency [ 19 ]. Conversely, iodine in excess is much less harmful as it may only affect a small percentage of sensitive individuals, whereas iodine deficiency can affect an entire cohort or parts of a population with endemic consequences [ 20 ].…”
Section: Discussionmentioning
confidence: 99%